Evaluation of stored potato (Solanum tuberosum L.) for soft rot bacteria in Ibadan, Nigeria - Durojaye Hammed Abiodun; Owoeye Tolulope Abisola (Journal of Agriculture and Applied Biology, 2021)
Potato (Solanum tuberosum L.) is a tuberous crop from the Solanaceae family which is a source of starch and food to many in Nigeria, however, its production is being hampered in field and storage by bacterial pathogen which causes rot of the stored tubers. To this end, the study aimed at screening potatoes from different stores within Ibadan for the evaluation and diversity of bacteria pathogens responsible for rot in potatoes. Damaged stored potato samples were collected from different locations in Ibadan for studies, these samples were isolated for bacterial pathogen and characterized biochemically and observed under the microscope for identification. Three genera of bacteria were observed to be responsible for potato rot in the study and they include Pectobacterium carotovorum, Pseudomonas syringae and Ralstonia solanacearum. Of all the isolated bacteria, Pectobacterium carotovorum has the highest occurrence with a frequency of 60%, while Pseudomonas syringae has a frequency of 33% and Ralstonia solanacearum has a frequency of 27%. The pathogenicity of the isolates were tested and this revealed that Pectobacterium carotovorum is the most virulent with a severity score of 4.3, while Ralstonia solanacearum follows with a score of 3.3 and a score of 2.7 was recorded for Pseudomonas syringae, while the control had a score of 0. The diversity and differences shown in the isolated bacteria indicated that potato rot is a serious disease which is caused by different bacteria and need an integrated approach for its control from the field of harvesting to the storage house.